Policy on Giving Awards to Student Athletes in Bogor District - Gopur, Abdul; Nuryadi, Nuryadi; Mudjianto, Sufyar; Gumilar, Agus (JUMORA: Jurnal Moderasi Olahraga, 2025)
This study confirms that awards can increase athlete motivation if given with the right approach, such as informative feedback and an environment that supports athlete autonomy. With an effective policy, it is hoped that sports achievements in Bogor Regency can continue to increase, while also providing inspiration for other regions in designing similar policies. Analyzing the influence of budget and implementation on the effectiveness of the policy of awarding young athletes in Bogor Regency. Achievement sports are types that rely on skills to achieve certain targets, with a foundation of science and innovation in sports technology. To achieve optimal performance, an athlete must go through an intensive and focused training process. Without structured training, athletes will not be able to hone the skills needed to achieve their goals. Therefore, proper training management from an early age is very important in developing sports talent.The results of the study showed that partially, the budget variable had a significant effect on the policy with a significance value of 0.018 (p <0.05), while the implementation variable did not have a statistically significant effect. However, simultaneously, the budget and implementation together had a significant effect on the effectiveness of the policy